Women's Position in Patriarchal Kinship System - Harahap, Ikhwanuddin (Jurnal Ilmiah Peuradeun, 2020)
Spirit of gender equalities is currently stretching amid the strong patriarchal system in North Padang Lawas District North Sumatera. In terms of education, women get the same rights as men, even in some villages, more women go to school/college than men. There is a growing slogan that is "anak do boru, boru do anak" (boys and girls are the same). Women have the freedom to choose their own spouse and are not bound to the custom of "manyunduti". However, in the economic field, wives work in the fields and tore rubber to support the family's economy besides they have to do all the household works. Based on the gender perspective, this is a form of gender injustice, the namely double burden. Another form of inequality is in terms of inheritance, in which they get little part even in the form of giving (pangalehenan/ olongate). This is a form of marginalization experienced by women in North Padang Lawas District North Sumatera.